Transforming morphology into ecology: Functional trait-based estimation of biomass and carbon budget in predatory nematodes (Nematoda: Mononchida) - Ghaderi, Reza; Nielsen, Uffe N.; He, Ji-Zheng (Applied soil ecology : a section of Agriculture, ecosystems & environment, 2026)
Predatory nematodes in the order Mononchida play a key biological regulation role in soil food webs but remain underexplored in terms of their ecosystem functions. Estimating biomass using morphological traits provides a practical method for assessing their contribution to carbon dynamics. This study calculates individual biomass and daily carbon budgets for mononchids using taxon-specific body-size data from publicly available literature. We calculated biomass and carbon budgets for 398 populations worldwide, representing 234 species, 47 genera, 12 subfamilies, and 8 families using Andrássy's formula. The estimated average biomass (fresh weight) was 6.71 μg for females and 10.75 μg for males across all species with available body size measurements, with corresponding daily carbon budgets of 0.07103 μg and 0.10481 μg, respectively. Compared to previous estimates, our data support higher biomass and more contribution of predatory nematodes to carbon budget. Biomass variability was notable across certain taxa (typically taxa within the family Mononchidae) but not all. Additionally, we tested the G index (female gonad-to-body length ratio) as a proxy for carbon budget estimation but surprisingly found no significant correlation between these two parameters (r = 0.174, p = 0.087). This study provides a comprehensive dataset for biomass and carbon budget estimation in predatory nematodes, enhancing understanding of their functional roles in carbon dynamics and ecosystem processes. •Trait-based biomass estimated potential carbon budget in predatory nematodes.•Intra-taxon variability in biomass data was observed only in certain taxa.•Unlike body size traits, female gonad was not a good proxy for carbon budget.